In vitro cytotoxicity of montelukast in HAPI and SH-SY5Y cells. (1st August 2020) - Tseng, Yu-Ting; Cox, Tynan M.; Grant, Gary D.; Arora, Devinder; Hall, Susan; McFarland, Amelia J.; Ekberg, Jenny; Rudrawar, Santosh; Anoopkumar-Dukie, Shailendra
Abstract: Montelukast is a cysteinyl leukotriene (CysLT) receptor antagonist with efficacy against a variety of diseases, including asthma and inflammation-related conditions. However, various neuropsychiatric events (NEs) suspected to be related to montelukast have been reported recently, with limited understanding on their association and underlying mechanisms. This study aimed to investigate whether montelukast can induce neuroinflammation and neurotoxicity in microglial HAPI cells and neural SH-SY5Y cells. The present study also compared the effects of montelukast with a 5-lipoxygenase inhibitor (zileuton) and a cyclooxygenase-2 inhibitor (celecoxib) to better understand modulation of related pathways. HAPI or SH-SY5Y cells were treated with the indicated drugs (3.125 μM–100 μM) for 24 h to investigate drug-induced neuroinflammation and neurotoxicity. Montelukast induced cytotoxicity in HAPI cells (50–100 μM), accompanied with caspase-3/7 activation, prostaglandin E2 (PGE2 ) release, and reactive oxygen species (ROS) production. Whilst both montelukast and zileuton down-regulated CysLT release in HAPI cells, zileuton did not significantly affect cell viability or inflammatory and oxidative factors. Celecoxib decreased HAPI cell viability (6.25–100 μM), accompanied with increasing caspase-3/7 activation and ROS production, but in contrast to montelukast increased CysLT release and decreased PGE2 production. Similar to observations in HAPI cells, both montelukast and celecoxib (50–100 μM) but not zileuton produced toxicity in SH-SY5Y neuroblastoma cells. Similarly, CM from HAPI cells treated with either montelukast or zileuton produced toxicity in SH-SY5Y cells. The results of the current study show the capability of montelukast to directly induce toxicity and inflammation in HAPI cells, possibly through the involvement of PGE2 and ROS, and toxicity in undifferentiated SH-SY5Y neuroblastoma cells. The current study highlights the importance of consideration between benefit and risk of montelukast usage and provides references for future investigation on decreasing montelukast-related NEs. Highlights: This study provides the first in vitro evidence on Montelukast toxicity to microglial and neuronal cells. Provides evidence that this toxicity may be mediated by inflammatory response. Suggests that the inflammatory response and toxicity may contribute to neuropsychiatric events seen with montelukast use.